The Use Of Educational Games To Improve Students' Learning Motivation in Elementary School - Deviyanti Abdullah (AIQU: Journal Multidiscipliner of Science, 2024)
Online learning has become the primary solution in addressing educational challenges in the digital era. However, both students and parents continue to face various obstacles. One major issue arises when learning materials are too difficult and delivered using teaching resources that are hard to comprehend. This leads to a decline in students' interest and dedication to learning. Moreover, the inability of parents to fully support their children's learning process during online sessions further complicates the situation. Teaching media used by educators are often monotonous or unappealing, which fails to stimulate students’ comprehension effectively. As a result, children struggle to understand complex learning content. This study aims to evaluate the effectiveness of innovative and engaging learning media in improving students' understanding during online learning. The research uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects include teachers, students, and parents at the elementary school level. Findings from this study are expected to provide recommendations for the development of more adaptive and student-centered digital learning media tailored to the needs and characteristics of learners